Perencanaan Strategi Pemasaran Jasa Kalibrasi Dalam Menghadapi Persaingan Dengan Menggunakan Pendekatan Analisis SWOT dan AHP - Andhika Mayasari, Adisti Permata Cahya, Minto, Nur Muflihah, (Universitas Muria Kudus, 2023)
There are shipyard industry companies that provide measuring instrument calibration services. In 2022, the calibration service experienced a decline in marketing and a lack of external market segments compared to internal ones. This research aims to identify the factors that contributed to this decline, analyze marketing strategies using the SWOT analysis approach, and prioritize calibration service marketing strategies using the AHP method. The results of the SWOT analysis revealed four alternative strategies: SO (Strength-Weakness), WO (Weakness-Opportunity), ST (Strength-Threats), and WT (Weakness-Threats). In the IFAS and EFAS matrix, two influential factors were identified: licensing to enter the calibration laboratory location, which involves too much bureaucracy and makes customers hesitant to return (score of 0.45), and damaged calibrator standards that may lead to the suspension of calibration scope (score of 0.70). Based on the hierarchical structure, the AHP method prioritized the WT strategy with a weight of 5.11. This strategy includes conducting periodic checks, forecasting the calibrator to ensure good maintenance, and establishing cooperation with agencies that require calibration services. These prioritized strategies aim to increase sales and improve the marketing of calibration services for shipyard industry companies.